Neurorehabilitation in complex treatment of multiple sclerosis - I. A. Rybak; G. V. Kharlamova; S. V. Prokopenko (Бюллетень сибирской медицины)
The article provides the results of the research preformed with the purpose to study the efficiency of methods, focused on restoration of balance at patients with multiple sclerosis during exacerbation and remission stages. The received data testify to efficiency of a course of neurorehabilitation treatment for restoration of balance at multiple sclerosis both during exacerbation of and remission of the disease.